Effects of electric current frequencies, laser irradiation and combined treatment on Saccharomyces cerevisiae viability - Hamzić, Alen; Omerbašić, Ago; Eminović, Izet; Vladušić, Marija; Suljević, Damir (Acta Biologica Szegediensis, 2016)
In this research, we examined the influence of low voltage (9 V) electric current frequencies (1.4 and 17 Hz), laser irradiation (648 and 532 nm) and combined treatment (one frequency and one laser beam) on the viability of baker’s yeast (Saccharomyces cerevisiae). Each treatment was conducted using modified methods and equipment in air-filter equipped working chamber. Staining was performed by a non-vital/vital staining technique that has shown an increase in viability of all samples. Counting of yeast cells in 1 ml of sample gave us several positive results in terms of different treatments, cell viability and increase in the number of healthy cells. Treatment with electric current at higher frequencies (4 and 17 Hz) showed increased cell death counts and, although compensating by an increase in viability, the 17 Hz frequency was considered more hazardous. The most adequate treatments (both increased viability and cell count) were the combined treatments (1 Hz/4 Hz + one of the two laser beams). Although, all electric treatments show certain increases in cell viability, combined treatments (1 or 4 Hz coupled with green or red laser beam) show the most promise in achieving both increased cell viability and increased cell counts.